PELATIHAN PENGOLAHAN LIMBAH DAUN KOPI MENJADI TEH HERBAL DI DESA LEBAH SEMPAGA, NARMADA, KABUPATEN LOMBOK BARAT - Lale, Lale Fichear Neoningratheof; Aeni, Yuli; Ramadhan, Anugrah; Alamsyah, Ahmad; Mardiah , Al Aina Ul; Putri, Nabilah Tsabitah; Hamdi, M. Faizin Ilham; Putra, Sonny Manggala (Jurnal Bakti Nusa, 2025)
ABSTRACT Training on processing coffee leaf waste into herbal tea in Lebah Sempaga Village, Narmada, West Lombok Regency, aims to support tourism activities and improve the skills and knowledge of the community in managing abundant coffee leaf waste. So far, coffee leaf waste tends to be wasted, even though the potential for processing it into herbal tea has high economic value and is beneficial for health. This training includes various stages, starting from the collection of coffee leaves, sorting the separation of the stem from the leaves, washing in running water, drying process, roasting process, reducing coffee leaves (crushing), packaging herbal tea making into products. It is hoped that the results of this training can not only increase community income but also contribute to environmentally friendly waste management. In addition, this training emphasizes the importance of environmental sustainability and community awareness of the potential of natural resources around them.